Investigation and development of a numerical tool for the prediction and influence of natural fibre poroelastic trim behaviour on automotive cabin noise. Issue 1 (1st January 2018) - Dunne, R. K.; Desai, D. A.; Sadiku, R.
Abstract: In recent years, the automotive industry has been under increasing pressure to produce products that are environmentally friendly. Also, due to competition among automotive manufacturers and customer expectation, the automotive industry is under continuous pressure to reduce product lead time. Hence, in the automotive industry, there exists a need to reduce noise levels within the vehicle cabin and reduce product development time. Therefore, this research investigates the effect poroelastic materials have on the internal vehicle cabin noise levels due to the structural vibration induced from road/tyre interaction in the 20-200 Hz frequency range. This was achieved by developing an effective and efficient finite element analysis (FEA) tool that is capable of predicting the change in sound pressure levels (SPLs) due to the use of natural fibre trims in the vehicle cabin. A fully scaled (one fifth-scale) vehicle model using ABAQUS FEA software was developed, employing similarity scaling laws, in order to predict the influence various types of poroelastic trims have on internal vehicle noise. The results indicate that the implemented poroelastic materials reduced the SPL by as much as 2.935 dB. Thereafter, a fully scaled experimental model was developed in order to validate the FEA model developed. Validation of the FEA model was achieved by performing a complete modal and SPL analyses on the experimental model and thereafter, the results were compared. The results indicate that the FEA model developed is capable of accurately predicting the influence that the inserted poroelastic natural fibre trims have on internal cabin noise levels.